Modern terminology of management: Anglicisms as a means of adaptation to new economic realities - I. O. Zakharova (Вестник университета)
The subject of this study is an important part of the latest terminology of the modern management sphere, namely, anglicisms. The purpose of the article is to determine the role of anglicisms as an effective means of adapting participants in management processes in Russia to modern economic conditions. On the example of about 100 business terms of English origin, the article gives a classification of anglicisms according to structure, methods of formation, frequency of use and areas of application in management, provides a decoding of the meanings of individual components of borrowings, which contributes to the best understanding and use of business management terminology by specialists. Anglicisms originally entered the Russian language to denote concepts and phenomena completely new to the Russian reality, their emergence, integration into the vocabulary of the Russian language and active use seem to be an inevitable process that meets the communicative needs of society. Due to their high communicative significance, anglicisms from business sphere have firmly entered the Russian lexicon and are widely used in it.